2017
DOI: 10.4314/ijs.v19i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organosomatic indices and histopathological changes in vital organs of <i>Clarias gariepinus</i> juveniles fed graded levels of boiled sunflower (<i>Helianthus annuus</i>) seed meal

Abstract: This study investigated the effects of substituting boiled sunflower seed meal (BSSM) for soybean meal (SBM) on the organosomatic indices and histopathological changes in the liver, kidney and intestine of Clarias gariepinus juveniles for fifteen weeks. BSSM was substituted for SBM at 0, 20, 40, 60, 80 and 100% in formulating six isonitrogenous (40% crude protein) and isocaloric (4651.5 Kcal/kg) diets. Diets were fed twice daily to triplicate groups of 360 C. gariepinus juveniles inside eighteen rectangular ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Concerning studies showing that vacuolization is a characteristic phenomenon in the identification of cellular stress, including salt stress, numerous authors have described vacuolization in response to various stress factors in rice [24], wheat [25], vegetables [26], cotton [27], rapeseed [28], soybean [29] and maize [30]. Researchers have also observed that diets containing oil from the world's three main oil crops-rapeseed [31], soybean [32] and sunflower [33]-induced hepatocyte vacuolization.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning studies showing that vacuolization is a characteristic phenomenon in the identification of cellular stress, including salt stress, numerous authors have described vacuolization in response to various stress factors in rice [24], wheat [25], vegetables [26], cotton [27], rapeseed [28], soybean [29] and maize [30]. Researchers have also observed that diets containing oil from the world's three main oil crops-rapeseed [31], soybean [32] and sunflower [33]-induced hepatocyte vacuolization.…”
Section: Introductionmentioning
confidence: 99%
“…The significantly (p<0.001) high liver (LIS), Heart (HIS), Kidney (KSI) and Gill (GSI) indices in fish fed control diets compared to the TCe diets indicated that these organs reduction in size could have been as result of deposition of toxic substance or antinutrients(Adesina, 2017). The increase in LSI value in an ideal environment is related to normal liver growth but, in cases of pollution, liver enlargement is associated with hyperplasia(Hoque et al 1998;Adesina , 2017;Sogbesan, 2007 and Adejinmi , 2000). The HSI observed in the fish fed 0% TCe-based diet (control diet) indicated normal liver growth resulting from dietary treatment without TCe seed meal at this level.…”
mentioning
confidence: 99%